Rethinking Moral Agency: Luciano Floridi and the Ethics of AI in the Age of ChatGPT - Sabu, Fransiskus Xaverius; Asmiyanto, Taufik (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2026)
Background: As Artificial Intelligence (AI) becomes increasingly pervasive, the technology must be viewed as more than a mere utility for task automation. To preserve human agency, AI integration should facilitate freedom of expression and prevent the systematic marginalization of human roles within the digital ecosystem. Purpose: This study provides a critical elaboration of Luciano Floridi’s Ethics of Information (EOI). The researchers aim to uncover the philosophical essence of Floridi’s thought regarding artificial agents and their moral status within the "infosphere." Methods: Utilizing a comprehensive philosophical literature review and critical analysis, the authors examine Floridi’s core tenets. The study maps the transition from traditional anthropocentric ethics to an information-centric moral framework. Findings: The study reveals that Floridi’s reflection on artificial agents necessitates a radical reassessment of moral accountability. By developing the concept of distributed morality, Floridi shifts the ethical burden from a single point of origin (the designer) to a collective, systemic responsibility that encompasses both the technological architecture and its end-users. Originality/Value: This research highlights a revolutionary ethical model that redefines the relationship between humans and artificial agents. By advocating for a non-anthropocentric approach to moral agency, the study provides a vital framework for ensuring that AI development remains aligned with humanistic values and collective ethical participation.